2017
DOI: 10.2527/jas2017.1790
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the drivers of improved pig weaning weight by investigation of colostrum intake, sow lactation feed intake, or lactation diet specification1

Abstract: Modern sows have low feed intake (FI) during lactation. The main aim of this study was to understand interactions between and separate effects of FI and nutrient density on litter weaning weight (WW). Key drivers of colostrum intake (CIn), piglet survival, WW, and colostrum yield (CY) were also investigated. Sows ( = 82) were offered a High (15.8 MJ/kg DE; 1.3% total lysine) or Normal (15.2 MJ/kg DE; 1.28% total lysine) specification lactation diet at either a High (feed allowance increased by 0.5 kg/d after f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…6 Total MUFA-monounsaturated fatty acids. 7 Total PUFA-polyunsaturated fatty acids. 8 Total n-3 PUFA-omega 3 fatty acids polyunsaturated fatty acids.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Total MUFA-monounsaturated fatty acids. 7 Total PUFA-polyunsaturated fatty acids. 8 Total n-3 PUFA-omega 3 fatty acids polyunsaturated fatty acids.…”
Section: Methodsmentioning
confidence: 99%
“…Park et al [6] found that a high energy diet (14.7 MJ/kg DE) in lactation reduced sow body weight and back-fat loss and increased piglet growth to weaning compared to a low energy diet (14.2 MJ/kg DE). Craig et al [7] also reported an increase in litter average daily gain when a high energy diet (15.8 MJ/kg DE) was offered compared to a 'normal' diet (15.2 MJ/kg DE). However, feed intake in sows commonly plateaus in late lactation due to limited gut capacity.…”
Section: Introductionmentioning
confidence: 97%
“…Growth during the rst days after birth can determine subsequent piglet survival and growth. Indeed, survival of piglets during lactation is correlated with piglet weight gain in the rst 48 hours after birth 29 . In addition, piglet survival is lower when colostrum intake is not su cient 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that the positive selections of Duroc are associated with specific genes related to lactation [4], reproduction [5] , meat quality [6], and growth traits [7]. Other studies have reported that the reproductive traits such as number of piglets born alive (NBA) [8], lactation capacity, litter weight at weaning (LWW) [9], and number of piglets weaned (NW) [10] all have been genetically improved through phenotypic or selective signatures.…”
Section: Introductionmentioning
confidence: 99%